2015
DOI: 10.1126/scitranslmed.3010467
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-dependent changes in interstitial ECM mechanics promote breast tumorigenesis

Abstract: Obesity and extracellular matrix (ECM) density are considered independent risk and prognostic factors for breast cancer. Whether they are functionally linked is uncertain. We investigated the hypothesis that obesity enhances local myofibroblast content in mammary adipose tissue and that these stromal changes increase malignant potential by enhancing interstitial ECM stiffness. Indeed, mammary fat of both diet- and genetically induced mouse models of obesity were enriched for myofibroblasts and stiffness-promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
325
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 278 publications
(341 citation statements)
references
References 59 publications
15
325
1
Order By: Relevance
“…Collagen fibers were quantified using ImageJ. Multiphoton second harmonic generation (SHG) imaging was used to characterize collagen quantity and collagen fiber length in rehydrated cross-sections of lungs using a custom-built multiphoton microscope as described previously (46).…”
Section: Preclinical Studymentioning
confidence: 99%
“…Collagen fibers were quantified using ImageJ. Multiphoton second harmonic generation (SHG) imaging was used to characterize collagen quantity and collagen fiber length in rehydrated cross-sections of lungs using a custom-built multiphoton microscope as described previously (46).…”
Section: Preclinical Studymentioning
confidence: 99%
“…In addition, cadherin-11 blockade may be relevant to other diseases linked by ECM deposition by cadherin-11-expressing fibroblasts or myofibroblasts. A recent study showed that obesity increases myofibroblasts and ECM stiffness in the adipose tissue of mammary fat and that changes in ECM mechanics promote breast tumorigenesis in obesity (49). It would be interesting to determine whether blocking cadherin-11 in the myofibroblasts of mammary fat can reduce the risk for breast tumorigenesis by inhibiting obesity-induced collagen production.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse microarchitectures of fibrillar collagen and the range of resulting biomechanics can result in very different microenvironments despite equivalent levels of collagen [83][84][85], which potentially explains the weak clinical link between collagen I and prognosis in older studies [86,87]. It remains difficult to decouple the effects of fiber diameter, pore size and biomechanics, but it appears that all three act on cells (reviewed in [88]).…”
Section: Microstructure Biomechanics and Crosslinkingmentioning
confidence: 99%